Pengaruh Sekam Padi & Serbuk Kayu Sebagai Substitusi Filler pada Campuran Laston AC-WC - Nugraha, Dwi Chandra; Agustapraja, Hammam Rofiqi (Universitas Batanghari Jambi, 2024)
Asphalt Concrete Wearing Course (AC-WC) is a flexible highway pavement, where this pavement is a combination of: Asphalt, fine aggregate coarse aggregate, and (filler). In this study, the replacement of Portland cement filler was carried out as an experiment with alternative materials, namely rice husk ash and wood sawdust. Where in this research mixture the percentage of cement filler is 2% replaced using 2% SP ash, 2% SK ash, 1% SP ash: 1% SK ash, in terms of Marshall properties In accordance with the standard requirements of General Specifications 2010 (revision 3) Section 6.3 Hot bituminous mix. From the Marshall test results, the highest stability value was 938.71 kg and a flow value of 2.83 mm by substituting 2% SP ash filler, where the resistance was better than the standard 2% cement filler mixture with a stability value of only 889.68 kg . The VIM value obtained was 3.57%, although it met the standard, the VIM value indicated that the 2% rice husk ash filler substitution mixture was not watertight. It can be seen that the high VMA value of 23.30% indicates the large number of cavities in the AC-WC mixture. Where the greater the percentage of VIM and VMA, the lower the adhesiveness of the asphalt mixture by substituting Cement filler using SP ash, as evidenced by the VFA value of only 52.41% which does not meet standard specifications, because the voids created will be filled with air or water. Replacement of 2% SP ash filler obtained a Marshall Quotient value of 333.70 kg/mm which met the specification standard, namely Min 250 kg/mm but higher than the normal 2% cement filler mixture which was only 258.23 kg/mm.